A Review of the Role of Wnt in Cancer Immunomodulation - Goldsberry, Whitney N. (Cancers (Basel), 2019)
Alterations in the Wnt signaling pathway are associated with the advancement of cancers; however, the exact mechanisms responsible remain largely unknown. It has recently been established that heightened intratumoral Wnt signaling correlates with tumor immunomodulation and immune suppression, which likely contribute to the decreased efficacy of multiple cancer therapeutics. Here, we review available literature pertaining to connections between Wnt pathway activation in the tumor microenvironment and local immunomodulation. We focus specifically on preclinical and clinical data supporting the hypothesis that strategies targeting Wnt signaling could act as adjuncts for cancer therapy, either in combination with chemotherapy or immunotherapy, in a variety of tumor types.